Synthesis and Bioactivity of Furoxan-Based Nitric Oxide-Releasing Colchicine Derivatives as Anticancer Agents - Hong Shen, Li; Li Wang, Sheng; Yu Li, Hong; Sheng Lai, Yi; Jie Liu, Li (Asian Journal of Chemistry, 2013)
A series of novel nitric oxide-donating colchicine derivatives (9a-j) were synthesized by coupling furoxan with N-methyl colchiceinamide through an appropriate spacer arm and their cytotoxicity against four human cancer cell lines in vitro were evaluated by MTT method. It was found that many of the derivatives displayed significant activity, particularly, compound 9f showed more potent cytotoxic activities than colchicine.